THE BADI’ FACE IN SERMON QASS BIN SAIDA AL-IYADI - Nur Halimah, Nafi; Jaida Azizah, Aufa (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This article explores the types of verbal escalation found in several sermon Qass bin Sa'ida al-Iyadi. The researcher uses Arabic rhetoric theory as written by Abd al-Rahman Hassan Habankah al-Maidani on the topic